Carbon supported bifunctional Rh–Ni(OH)2/C nanocomposite catalysts with high electrocatalytic efficiency for alkaline hydrogen evolution reaction. (1st April 2022) - Wang, Y.F.; Luo, X.; Lu, W.J.; Yang, L.; Huang, B.; Li, P.T.; Yang, Y.Q.
Abstract: Pt group metals display lower HER activity in alkaline solution than in acidic solution, because they are inefficient in the water dissociation step (Volmer step). Compared with Pt, the activity difference of Rh in alkaline and acidic media is much smaller. Meanwhile, Ni(OH)2 is proved to be an effective catalyst for water dissociation. Therefore, Rh–Ni(OH)2 /C nanocomposites with different Rh:Ni(OH)2 ratios were synthesized by a co-deposition/partial reduction method, and their microstructures as well as electrocatalytic properties were studied. The results show that Rh and Ni(OH)2 display synergistic effect in Rh–Ni(OH)2 /C nanocomposites. The Rh–Ni(OH)2 /C nanocomposite with a molar ratio of Rh to Ni(OH)2 of 1:1 exhibits the highest activity. It shows an overpotential of 36 mV at 10 mA cm −2 and a Tafel slope of 32 mV dec −1 for HER in alkaline media, which is superior to commercial Pt/C. In addition, the Rh–Ni(OH)2 /C (1:1) nanocomposite shows excellent durability in alkaline media as well. Highlights: A set of Rh–Ni(OH)2 /C nanocomposite catalysts were synthesized by a co-deposition/partial reduction method. The degree of dispersion of Rh and Ni(OH)2 nanoparticles on carbon spheres was influenced by Ni(OH)2 content. Rh and Ni(OH)2 display synergistic effect in Rh–Ni(OH)2 /C nanocomposites in alkaline solution. The Rh–Ni(OH)2 /C nanocomposite with a molar ratio of Rh to Ni(OH)2 of 1:1 exhibits superior HER catalytic activity. The combined use of Ni(OH)2 and Rh provides a way of designing low-cost and high efficient HER electrocatalysts.